Vegetation analysis along the altitudinal gradient of Mt. Ilong, Halcon Range, Mindoro Island, Philippines - ELAINE LOREEN C. VILLANUEVA; INOCENCIO E. BUOT, JR. (Biodiversitas Journal of Biological Diversity, 2018)
Villanueva ELC, Buot, JrIE. 2018. Vegetation analysis along the altitudinal gradient of Mt. Ilong, Halcon Range, Mindoro Island, Philippines. Biodiversitas 19: 2163-2174. The vegetation of Halcon Range is diverse, unique, and culturally important; however, there is a very limited information on its altitudinal distribution and structure, leading to the formation of land uses that trigger problem in sustainable management decisions for the mountain. This study analyzed the vegetation in land use types distribution along the altitudinal gradient of Mt. Ilong, Halcon Range, Mindoro, Philippines. Fourteen plots of 10 x 10m were established along the slope from 100m-1400m elevation. The tree species that were sampled from the plots were subjected to classification and ordination analyses. The dendrogram showed three distinct vegetation zones corresponding land use types: Zone I (agroforest land use zone), Lansium-Artocarpus-Swietenia-Ficus-Nephelium-Mangifera zone; Zone II (forest land use zone), Cyathea-Astronia-Syzygium-Garcinia-Ficus-Psydrax-Diplodiscus zone; and Zone III (forest land use zone), Agathis-Suli-Alitugba-Ardisia zone. Canonical correspondence analysis (CCA) indicated that elevation, temperature and pH level are the environmental variables that strongly influenced the vegetation distribution in various land uses, a characteristic that is similar to other tropical mountains.